2015
DOI: 10.1108/jsm-02-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Customer and employee co-creation of radical service innovations

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 43 publications
5
67
0
Order By: Relevance
“…While previous studies (Ngo and O'Cass, ) advocate for a positive relationship between customer integration and service innovations, the presented results do not particularly highlight customer integration as an important factor. Several explanations may be offered: first, this article investigates radical service innovations, and it has been previously shown that for radical innovations customer integration is not necessarily beneficial or not equally beneficial in different stages of the service development (Melton and Hartline, ); second, the sample of the present study consists of manufacturing SMEs striving to servitize their offerings—this may make an important difference in the self‐conception of how to pursue innovation. Service companies from the outset may have a greater proximity to the customer and may use their services to integrate the customer as a resource.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies (Ngo and O'Cass, ) advocate for a positive relationship between customer integration and service innovations, the presented results do not particularly highlight customer integration as an important factor. Several explanations may be offered: first, this article investigates radical service innovations, and it has been previously shown that for radical innovations customer integration is not necessarily beneficial or not equally beneficial in different stages of the service development (Melton and Hartline, ); second, the sample of the present study consists of manufacturing SMEs striving to servitize their offerings—this may make an important difference in the self‐conception of how to pursue innovation. Service companies from the outset may have a greater proximity to the customer and may use their services to integrate the customer as a resource.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the research question, service‐dominant logic (SDL) is applied as the theoretical lens. SDL is particularly suitable for an analysis to explain how manufacturing companies are able to introduce significant (radical) service innovations on the market, because SDL incorporates four factors that researchers consider to be significant for influencing the innovation activities nowadays: the actor value network , which in SDL considers the importance of value creation in a network that goes beyond the boundaries of the company (Chesbrough, ); resource liquefaction , which in SDL is related to the major shifts and opportunities driven by digitalization (Troilo, De Luca, and Guenzi, ); resource density , which in SDL is the requirement that companies activate and combine necessary resources most effectively and efficiently in order to provide value to the market (Lusch, Vargo, and Tanniru, ); and resource integration , which in SDL is the factor describing integration of the customer as a resource in value co‐creation (Melton and Hartline, ; Perks, Gruber, and Edvardsson, ). Methodologically, this research responds to recent calls for in‐depth analysis to present a more fine‐grained understanding of service innovation (Biemans et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of ideas supports the importance of actively involving users for leveraging service success (Trischler et al, 2017, Melton andHartline, 2015). It is the user who creates value in their specific context (Vargo and Lusch, 2008), implying that the design and provision of a value proposition needs to essentially start with clearly understanding the specific circumstances surrounding their value creational processes (Gustafsson et al, 2012).…”
Section: Please Insert Table 5 About Herementioning
confidence: 87%
“…For example, Weeks (2014) stresses the importance of resilience (anticipating and adjusting to environmental trends), while Liu et al (2015) found that corporate performance is related to how well the firm reacts to environmental complexity. There are two approaches to using marketing tactics effectively in complex and turbulent environments: stabilizing or destabilizing approaches (Nilson, 1995;McGlone and Ramsey, 1998;Melton and Hartline, 2015). Theodiridis (2009) suggests a similar approach of either absorbing, or adapting to, complexity.…”
Section: Complexity Marketing Approachesmentioning
confidence: 99%
“…Thus, destabilization can be either small, seemingly insignificant actions that influence the environment, or large dramatic actions that cause dramatic shifts in the environment. However, it must be remembered that, although the outcome is uncertain, such risk-taking leads to greater marketing competencies and innovation in turbulent environments, especially when related to product or service development (Garcia, 2004;Melton and Hartline, 2015). Further, Droge et al (2009) showed that innovativeness is linked to new product success in turbulent markets.…”
Section: Complexity Marketing Approachesmentioning
confidence: 99%